Comparison of surgical times between manual and robot-assisted epiretinal membrane peeling - Eberle, Alexander; Turgut, Ferhat; Somfai, Gábor Márk; Saad, Amr; de Smet, Marc D.; Hasler, Pascal W.; Heussen, Florian M.; Becker, Matthias D. (Translational Vision Science & Technology, 2024)
Epiretinal membranes (ERM) pose a common challenge in vitreoretinal pathology, often causing vision impairment in older adults. The Preceyes Surgical System (PSS) supports the surgical removal of ERM through robot-assisted membrane peeling (RA-MP). This study compares surgical times and iatrogenic hemorrhages between manual membrane peeling (MMP) and RA-MP using PSS. Nine patients underwent RA-MP with PSS, whereas 16 patients (18 eyes) underwent MMP for comparative analysis. Surgical durations were categorized into RA-MP, manual forceps utilization in PSS surgeries (mRA-MP), and traditional MMP. Cumulative manual manipulation duration (cMMP), instrument grasps, and intraoperative hemorrhages were statistically analyzed using the Mann-Whitney U test. RA-MP showed significantly longer peeling times compared to MMP (P < 0.001). Flap initiation grasps were similar between methods (P = 0.86), RA-MP demonstrated a significant reduction in peeling grasps (P = 0.01) and mean grasps per minute (P < 0.001). Although RA-MP resulted in fewer hemorrhages, the difference did not reach statistical significance relative to MMP (P = 0.08). Although RA-MP tended to extend surgical time, it offered advantages in reducing tissue trauma and intraoperative hemorrhages. Further research is needed to explore the learning curve for novice surgeons and evaluate the safety profile of RA-MP. RA-MP may offer potential advantages over manual surgery, particularly in terms of reduced tissue trauma and intraoperative hemorrhages. Despite its longer duration compared with manual techniques, RA-MP may lead to fewer grasping maneuvers and lower rates of hemorrhages, thereby enhancing the safety and precision of vitreoretinal surgeries.